Mechanical factors play an important role in pectus excavatum with thoracic scoliosis - Wang, Yuncang (BioMed Central, 2012)
BACKGROUND: This study investigated the incidence, imaging characteristics and mechanical factors in scoliotic patients with pectus excavatum. METHODS: A total of 142 scoliostic patients with pectus excavatum were evaluated prior to operation. The evaluation included a complete physical exam, phenotype and severity of the pectus excavatum, incidence and severity of scoliosis, and analysis of radiological images, including calculation of the Haller index. RESULTS: Twenty five out of 142 patients (17.61%) with pectus excavatum had scoliosis with a Cobb angle >10 degrees, and in 80.00% of the cases the spinal column was bent to the right. Seventeen patients had bent-to-the-right spines that involved the 6th to 10 th thoracic vertebrae. We found that 23 out of 25 patients with a Cobb angle more than 10° were teenagers and adults. The incidence of scoliosis was only 6.06% in the children under 11 years whereas it was 21.79% in the teenage group. CONCLUSIONS: Mechanical forces appear to play a role in the coexistence of pectus excavatum and scoliosis. There is a relationship between age, severity (Haller index), asymmetry and scoliosis. The heart and mediastinum play a role in providing an outward force to the left of the sternum which may be an important reason for the coexistence of pectus excavatum and scoliosis, but the correlation needs further proof.